Injection of Botulinum Toxin a to Upper Esophageal Sphincter for Oropharyngeal Dysphagia in Two Patients with Inclusion Body Myositis - Louis WC Liu; Mark Tarnopolsky; David Armstrong (Canadian Journal of Gastroenterology)
Inclusion body myositis (IBM) is a progressive degenerative skeletal muscle disease leading to weakening and atrophy of both proximal and distal muscles. Dysphagia is reported in up to 86% of IBM patients. Surgical cricopharyngeal myotomy may be effective for cricopharyngeal dysphagia and there is one published report that botulinum toxin A, injected into the cricopharyngeus muscle using a hypopharyngoscope under general anesthesia, relieved IBM-associated dysphagia. This report presents the first documentation of botulinum toxin A injection into the upper esophageal sphincter using a flexible esophagogastroduodenoscope under conscious sedation, to reduce upper esophageal sphincter pressure and successfully alleviate oropharyngeal dysphagia in two IBM patients.